IMPLEMENTATION OF THE VIGENERE CRYPTOGRAPHY ALGORITHM IN THE LHOKSEUMAWE STATE POLYTECHNIC CLOUD STORAGE SYSTEM - Dede Kurniawan; Indrawati; Hari Toha Hidayat; Martin Uribe (Bulletin of Engineering Science, Technology and Industry, 2023)
Cloud storage is a technology used to store data online. However, this technology also poses problems in terms of security. Therefore, the author wants to build a cloud storage system by implementing cryptographic security to secure data. By implementing cryptographic techniques in cloud storage, users don't need to worry about data loss or theft. The cryptographic method applied is the Vigenere Cipher algorithm, which is a classic type of cryptography. Cloud storage is applied to public and private networks to test the comparison of data encryption times. Based on tests carried out, implementation on private networks is better with an average time of 3.84 seconds for encryption and 253.6 milliseconds for decryption. Meanwhile, on public networks, the average time is 45.3 seconds for encryption and 392 milliseconds for decryption. To measure whether cryptography is effective or not, the avalanche affect method is used which produces a value of 1.4% to 7% with an average of 3.92%.